The association between smoking and the occurrence of hyperuricemia: A retrospective cohort study - Peihua Li+; Xinyu Li+; Guosheng Li+; Bing Wang; Yudan Liu; Yuedong Zhao; Qing Yu; Zhengnan Gao; Xuhan Liu (Tobacco Induced Diseases, 2025)
Introduction A retrospective cohort study was conducted to study the association between smoking and hyperuricemia (HUA).